Pseudomonas aeruginosa necrotizing bronchopneumonia - Ranjit I Kylat (University of São Paulo, 2021)
Extremely low birth weight (ELBW) infants are at particularly high risk for infection due to an immature immune system, invasive procedures such as endotracheal intubation, intravascular catheterization, and other factors. Neonatal infections in this population are associated with a high mortality, poor growth, and neurodevelopmental outcomes. Pseudomonas aeruginosa (P. aeruginosa) infection is an uncommon but potentially devastating cause of pneumonia and sepsis in the ELBW population. P. aeruginosa is an important cause of healthcare-associated infections (HAI) or nosocomial infections. P. aeruginosa can perceive unfavorable environmental changes and orchestrate adaptations by developing plasmid-mediated and adaptive resistance to antibiotics. We describe an ELBW infant born at 26 weeks' gestation who succumbed at 13 days of life to P. aeruginosa infection. Some of the factors related to the pathogenesis and multidrug resistance are described.